Do rates of dental wear in extant African great apes inform the time of weaning?. Issue 163 (February 2022) - Romero, Alejandro; Pérez-Pérez, Alejandro; Atiénzar, Gabriel García; Martínez, Laura M.; Macho, Gabriele A.
Abstract: Reconstructing the life histories of extinct hominins remains one of the main foci of paleoanthropological inquiry, as an extended juvenile period impacts the social and cognitive development of species. However, the paucity of hominin remains, the lack of comparative hominoid data, and the destructive nature of many life history approaches have limited our understanding of the relationship between dental development (eruption) and weaning in primates. Alternatively, the rate of dental wear in early-forming teeth has been suggested a good proxy for the timing of weaning. Here we test this hypothesis on an ontogenetic series of Gorilla gorilla gorilla and Pan troglodytes troglodytes, using geographic information systems–based shape descriptors of M1 s in relation to the nitrogen (δ 15 N) and carbon (δ 13 C) isotope composition of their associated hair. Results show that Gorilla g. gorilla are fully weaned considerably later than Pan t. troglodytes, that is, after M1s had been in full functional occlusion for some time. Yet, throughout ontogeny, gorilla dental wear rates are greater than they are in chimpanzees. This refutes the hypothesis that the rates of wear of early-forming teeth inform the time of weaning (i.e., nutritional independence). Instead, dietary breadth and seasonal variation in resource availability are implicated. This finding has implications for interpreting the hominin fossil record and raises questions about the triggers for, and the mechanisms of, life history change in hominin evolution. As a case in point, commonalities in life history patterns between early hominins and Western lowland gorillas seem to be a means to mitigate the effects of recurrent (i.e., seasonal) resource limitations and—conceivably—to prevent high infant mortality rates. Taken further, difference between hominid life histories are likely to be of degree, not kind.